2015
DOI: 10.1007/s10162-015-0515-y
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Changes of the Inner ear in Rhesus Monkeys After Intratympanic Gentamicin Injection and Vestibular Prosthesis Electrode Array Implantation

Abstract: Bilateral vestibular deficiency (BVD) due to gentamicin ototoxicity can significantly impact quality of life and result in large socioeconomic burdens. Restoring sensation of head rotation using an implantable multichannel vestibular prosthesis (MVP) is a promising treatment approach that has been tested in animals and humans. However, uncertainty remains regarding the histopathologic effects of gentamicin ototoxicity alone or in combination with electrode implantation. Understanding these histological changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…Although failure of vestibular reflexes can be caused by downstream lesions in the central nervous system, it often results from hair cell injury, dysfunction, or death caused by ototoxic injury (e.g., by gentamicin and other aminoglycoside antibiotics), ischemia, infection, Ménière's disease, or genetic inner ear abnormalities (11). For many such cases, the insult spares primary vestibular afferent neurons (12). When vestibular nerve branches to the 3 canals are at least partially intact, prosthetic electrical stimulation encoding head motion should provide an effective means of partially restoring vestibular sensation and alleviating BVL symptoms.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
See 1 more Smart Citation
“…Although failure of vestibular reflexes can be caused by downstream lesions in the central nervous system, it often results from hair cell injury, dysfunction, or death caused by ototoxic injury (e.g., by gentamicin and other aminoglycoside antibiotics), ischemia, infection, Ménière's disease, or genetic inner ear abnormalities (11). For many such cases, the insult spares primary vestibular afferent neurons (12). When vestibular nerve branches to the 3 canals are at least partially intact, prosthetic electrical stimulation encoding head motion should provide an effective means of partially restoring vestibular sensation and alleviating BVL symptoms.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
“…Species-specific differences in sensitivity to aminoglycoside antibiotics could play a role, as could differences in gentamicin dose, route of delivery to the labyrinth, subject age, and duration since the onset of ototoxic injury. However, adult nonhuman primates treated with gentamicin at doses sufficient to permanently wipe out natural VOR responses can still have robust electrically evoked 3D VOR responses years later, despite postmortem histologic exam revealing absence of type I hair cells and absence of stereocilia on type II hair cells (12). Human subjects in this study may have had even more severe hair cell lesions, but the presence of some natural VOR responses to whole-body rotation preoperatively suggests that they had at least some hair cell and afferent neuron survival.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
“…In animal models, vestibular deficit is typically induced either by gentamicin treatment or canal plugging. Both render the semicircular canals insensitive to rotation, but leave the afferent fibers intact and excitable by electrical stimulation (Lewis et al 2010, Sun et al 2015. In addition, canal plugging is unlikely to alter the spontaneous firing rate, while gentamicin treatment can reduce it by 40% in chinchillas (Hirvonen et al 2005).…”
Section: Effects Of Pulse Modulation On Peak Eye Velocitymentioning
confidence: 99%
“…Electrically evoked VOR (eVOR) induced by vestibular implants have also been realized to match the same frequency dependency of a normal human vestibular system (van de Berg et al, 2014 ). Histopathological examination has shown that multichannel vestibular prosthesis can target vestibular afferent fibers without damaging them (Sun et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%